1990
DOI: 10.1023/a:1015842600189
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The GI transit of radiolabeled sustained-release ibuprofen 800-mg tablets in eight healthy, fed volunteers was monitored using external gamma scintigraphy. Ibuprofen serum concentrations were determined from blood samples drawn over 36 hr following dosing. Sustained-release ibuprofen tablets containing 0.18% of 170Er2O3 (greater than 96% 170Er) in the bulk formulation were manufactured under pilot-scale conditions and were radiolabeled utilizing a neutron activation procedure which converted stable 170Er to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…One way in which kinetics have been measured with a single photon emitter was when the kinetics of interest were of the dosage form rather than of the drug. The tracer was included in a solid formulation in a way that reliably traced the solid [53,[119][120][121][122][123][124][125][126]. Quantification of the tracer was not required.…”
Section: Drug Kineticsmentioning
confidence: 99%
“…One way in which kinetics have been measured with a single photon emitter was when the kinetics of interest were of the dosage form rather than of the drug. The tracer was included in a solid formulation in a way that reliably traced the solid [53,[119][120][121][122][123][124][125][126]. Quantification of the tracer was not required.…”
Section: Drug Kineticsmentioning
confidence: 99%
“…Other bioequivalence studies have found that the addition of ibuprofen can lead to an increase in the rate of absorption of acetaminophen [15,16]. The ingestion of food can alter the rate and extent of drug absorption and this has been shown to occur with both acetaminophen and ibuprofen previously [16][17][18][19][20][21][22][23][24]. This study aimed to determine and compare the pharmacokinetic parameters (C max , AUC (0-t) , AUC (0-∞) , t max , K el , and t 1/2 ) of the four fixed-dose formulations of acetaminophen and ibuprofen (FDC500/150, FDC325/97.5, Sachets, Oral Suspension) in either fed or fasting conditions.…”
Section: Introductionmentioning
confidence: 99%